1994
DOI: 10.1523/jneurosci.14-11-06992.1994
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence imaging of extracellular purinergic receptor sites and putative ecto-ATPase sites on isolated cochlear hair cells

Abstract: Fluorescence imaging of extracellular adenosine-5′-triphosphate (ATP) binding sites on inner and outer hair cells isolated from the guinea pig organ of Corti was achieved using the fluorescent analog of ATP, 2′- (or-3′)-O-(trinitrophenyl)adenosine-5′- triphosphate (TNP-ATP; 30–75 microM). This analog, which fluoresces on binding to these sites, was pressure applied by micropipette while hair cells were viewed by fluorescence microscopy. Fluorescence imaging revealed a widespread distribution of extracellular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 70 publications
3
46
0
Order By: Relevance
“…Part of such discrepancy may be due to the age of animals investigated, since transient expression in certain developmental stages has been shown in each subtype (P2X 2 , P2X 3 , and P2X 7 ). However, among them, consistent results show that the P2X ionotropic channels are localized at the endolymphatic surface [4], especially at the stereocilia [9], and Na + influx through these channels was visualized using fluorescence [5]. More specifically, the P2X 2 receptor subtype was shown to be localized at the stereocilia of guinea pig hair cells [9], and therefore this may be the dominant P2X subtype.…”
Section: Ihcmentioning
confidence: 70%
See 1 more Smart Citation
“…Part of such discrepancy may be due to the age of animals investigated, since transient expression in certain developmental stages has been shown in each subtype (P2X 2 , P2X 3 , and P2X 7 ). However, among them, consistent results show that the P2X ionotropic channels are localized at the endolymphatic surface [4], especially at the stereocilia [9], and Na + influx through these channels was visualized using fluorescence [5]. More specifically, the P2X 2 receptor subtype was shown to be localized at the stereocilia of guinea pig hair cells [9], and therefore this may be the dominant P2X subtype.…”
Section: Ihcmentioning
confidence: 70%
“…8 of [29]). Studies using fluorescent imaging of Na + influx confirmed the apical location of ionotropic receptors, facing the endolymphatic compartment [4,5]. To date, there have been few reports on differential expression of P2 receptors along the basilar membrane, i.e., basal, middle, and apical turns.…”
Section: Ihcmentioning
confidence: 87%
“…PPADS is a nonselective P2 antagonist, but has the advantage that it associates and dissociates approximately 100 to 10,000 times more slowly than other known antagonists PATHOPHYSIOLOGY AND THERAPEUTIC POTENTIAL OF PURINERGIC SIGNALING (Spelta et al, 2002). The trinitrophenyl-substituted nucleotide TNP-ATP is a very potent antagonist at both P2X 3 and P2X 2/3 receptors (Mockett et al, 1994;King et al, 1997;Virginio et al, 1998;Burgard et al, 2000;Honore et al, 2002). A-317491 is a potent and selective non-nucleotide antagonist of P2X 3 and P2X 2/3 receptors, and it reduces chronic inflammatory and neuropathic pain in the rat (Jarvis et al, , 2004McGaraughty et al, 2003).…”
Section: Painmentioning
confidence: 99%
“…However, these compounds are relatively nonselective and exhibit high nanomolar-to-high micromolar affinities for P2X receptors (Bianchi et al, 1999). The ATP analog 2Ј,3Ј-O-(2,4,6-trinitrophenyl) adenosine 5Ј-triphosphate (TNP-ATP) has been used as a probe for more than two decades to label ATP-binding sites on a variety of tissues (Hiratsuka and Uchida, 1973;Watanabe and Inesi, 1982;Mockett et al, 1994). Mockett et al (1994) and King et al (1997) were among the first to describe the antagonist effects of TNP-ATP at P2X receptors.…”
mentioning
confidence: 99%
“…The ATP analog 2Ј,3Ј-O-(2,4,6-trinitrophenyl) adenosine 5Ј-triphosphate (TNP-ATP) has been used as a probe for more than two decades to label ATP-binding sites on a variety of tissues (Hiratsuka and Uchida, 1973;Watanabe and Inesi, 1982;Mockett et al, 1994). Mockett et al (1994) and King et al (1997) were among the first to describe the antagonist effects of TNP-ATP at P2X receptors. However, it was not until recently that Virginio et al (1998) described the selective antagonism of P2X 1 , P2X 3 , and P2X 2/3 receptors by low nanomolar concentrations of TNP-ATP.…”
mentioning
confidence: 99%